(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2025)
This paper proposes the analysis of sources from a feminist perspective that allow the reconstruction of sexuality, contraception and eugenic discourses in the National Territory of La Pampa between 1900-1943. The records consulted comprise the territorial/local press, reports of abortion and illegal practice of obstetric medicine, municipal records, notebooks of Health Visitors and infractions to Law 12.331 of Venereal Disease Prophylaxis. Although these sources cover diverse possibilities to identify the concepts of interest, at the same time they contain limits linked to the morality of the time and to the androcentrism in scientific production.